The Influence of Learning Management and Achievement Motivation on Students’ Learning Achievement - Melda, Bernadeta; Rosani, Meilia; Indrawati, Sri Wahyu (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2025)
This study investigates the effects of learning management and achievement motivation on student learning achievement in State Elementary Schools in Sako District, Palembang, Indonesia. A quantitative approach with an ex-post facto design was employed. Data were collected via questionnaires from 160 teachers across State Elementary Schools in Sako District. Descriptive statistics and multiple regression analysis were used to examine the relationships between variables. The findings indicate that (1) learning management significantly influences student learning achievement, (2) achievement motivation significantly affects student learning achievement, and (3) both learning management and achievement motivation collectively have a significant impact on student learning achievement. This study provides empirical evidence on the combined influence of learning management and achievement motivation on student outcomes in the context of Indonesian elementary education, a less explored area in existing literature. The results suggest that enhancing teachers' learning management strategies and fostering achievement motivation can improve student performance. School administrators and policymakers should consider targeted training programs for teachers to optimize these factors. This study contributes to educational research by validating the importance of instructional and motivational factors in student achievement, offering insights for educators and stakeholders in similar socio-cultural contexts.